2016
DOI: 10.1002/ldr.2476
|View full text |Cite
|
Sign up to set email alerts
|

Historical Land‐use and Vegetation Change in Northern Kwazulu‐Natal, South Africa

Abstract: The role of anthropogenic activity is increasingly recognized as an agent of environmental change. Photographs, taken more than 130 years ago in KwaZulu-Natal, South Africa, show a very different landscape to that viewed today. In attempting to understand some of the dynamics behind the changes in the landscape, we explored the history of land-use in communal rangelands in KwaZulu-Natal from the arrival of Iron Age man through to modern practices. Communal farming is frequently cited as a major cause of enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…The degradation of soil and reduction of vegetation cover caused by human activity are increasing globally as a consequence of agriculture, grazing, mining and urban developments (Bruun et al, 2015;Ferreira de Araújo et al, 2015;Ochoa et al, 2016;Russell and Ward, 2016). The loss of soil quality causes a loss in soil functional activities, and this results in the loss of the ecosystem services, resources and goods that these soils offer to humankind; these in turn have important negative effects on the geochemical, hydrological, and biological Earth System cycles (Berendse et al, 2015;Brevik et al, 2015;Decock et al, 2015;Smith et al, 2015;Keesstra et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The degradation of soil and reduction of vegetation cover caused by human activity are increasing globally as a consequence of agriculture, grazing, mining and urban developments (Bruun et al, 2015;Ferreira de Araújo et al, 2015;Ochoa et al, 2016;Russell and Ward, 2016). The loss of soil quality causes a loss in soil functional activities, and this results in the loss of the ecosystem services, resources and goods that these soils offer to humankind; these in turn have important negative effects on the geochemical, hydrological, and biological Earth System cycles (Berendse et al, 2015;Brevik et al, 2015;Decock et al, 2015;Smith et al, 2015;Keesstra et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We need better comprehension of the impact of abandonment on water resources (López-Vicente et al, 2016), soil properties (Novara et al, 2015;Brevik et al, 2016;Nadal-Romero et al, 2016) and its impact on the chemical composition of the atmosphere due to changes in the carbon cycle induced by the abandonment (Gabarrón-Galeote, 2016a;2016b;Nadal-Romero et al, 2016;Novara et al, 2016). Although land abandonment mainly occurred in developed countries during the last century and this is where most of the research has been conducted (Shelef et al, 2015), it is now also a process found in developing countries such as some regions of Ethiopia (Mekonnen et al, 2015;Tesfahunegn et al, 2016), China (Kou et al, 2016;Tengberg et al, 2016;Yu et al, 2016), South Africa (Russell and Ward, 2016) and South America (Ochoa-Cueva et al, 2015;Trabaquini et al, 2015). To this point scientific research has mainly focused on the impact of abandonment from the pedological (Giménez-Morera et al, 2010;Brevik, 2013;Bruun et al, 2015;Colazo and Buschiazzo, 2015), hydrological (Keesstra, 2007;Keesstra et al, 2009;Nadal-Romero et al, 2011;Serrano-Muela et al, 2015;Sanjuán et al, 2016), biological (Russell and Ward, 2016;van Hall et al, 2016), geomorphological (Nadal-Romero et al, 2015), and landscape (Lasanta et al, 2015a(Lasanta et al, , 2015b) points of view.…”
Section: Introductionmentioning
confidence: 99%
“…Although land abandonment mainly occurred in developed countries during the last century and this is where most of the research has been conducted (Shelef et al, 2015), it is now also a process found in developing countries such as some regions of Ethiopia (Mekonnen et al, 2015;Tesfahunegn et al, 2016), China (Kou et al, 2016;Tengberg et al, 2016;Yu et al, 2016), South Africa (Russell and Ward, 2016) and South America (Ochoa-Cueva et al, 2015;Trabaquini et al, 2015). To this point scientific research has mainly focused on the impact of abandonment from the pedological (Giménez-Morera et al, 2010;Brevik, 2013;Bruun et al, 2015;Colazo and Buschiazzo, 2015), hydrological (Keesstra, 2007;Keesstra et al, 2009;Nadal-Romero et al, 2011;Serrano-Muela et al, 2015;Sanjuán et al, 2016), biological (Russell and Ward, 2016;van Hall et al, 2016), geomorphological (Nadal-Romero et al, 2015), and landscape (Lasanta et al, 2015a(Lasanta et al, , 2015b) points of view. There is also an economic issue behind abandonment due to the lack of income for farmers, and there is an interest in the use of abandoned agriculture fields to increase soil carbon sequestration (Alexander et al, 2015) as once the land is abandoned there may be an increase in soil organic matter as new vegetation grows and covers the soil with a consequent sequestration of carbon (Cerdà et al, 2014;Hombegowda et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Grassland phenology dynamics are closely related to spring precipitation and increasing temperature at the early growing period (Gong et al, 2015). Also, the vegetation changes are affected by other factors, such as anthropogenic activity (Kou et al, 2015;Russell and Ward, 2016).…”
Section: Correlations Analysismentioning
confidence: 99%